2005
DOI: 10.1163/156854105774384750
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the ITS rDNA and identification of Nacobbus aberrans (Thorne, 1935) Thorne & Allen, 1944 (Nematoda: Pratylenchidae) by rDNA amplification

Abstract: In order to identify the false root-knot nematode, Nacobbus aberrans, a nematode of quarantine importance, investigations were undertaken at the molecular level. Study of the ITS rDNA region among six South American populations showed an extremely high polymorphism. This polymorphism is due to point mutation insertions-deletions, the importance of which is increased by the presence of a degenerate microsatellite in this region. The usefulness of the ITS rDNA is therefore questionable when designing a species-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 3 publications
(5 reference statements)
1
21
0
2
Order By: Relevance
“…In fact, the statistical results support the existence of two separate groups: one group composed of Argentinean, Bolivian and Peruvian populations, and another one composed of one Argentinean population. These results agree with those obtained by molecular approaches with the same populations (Anthoine & Mugniéry, 2005) and also with other population sets (Ibrahim et al, 1997;Reid et al, 2003). Despite their variability, N. aberrans populations grouped according to their geographical origin: South American vs North American populations, except for the Argentinean populations which divide between the two groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, the statistical results support the existence of two separate groups: one group composed of Argentinean, Bolivian and Peruvian populations, and another one composed of one Argentinean population. These results agree with those obtained by molecular approaches with the same populations (Anthoine & Mugniéry, 2005) and also with other population sets (Ibrahim et al, 1997;Reid et al, 2003). Despite their variability, N. aberrans populations grouped according to their geographical origin: South American vs North American populations, except for the Argentinean populations which divide between the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…Initial material was composed of infected roots. All Nacobbus populations were identified as N. aberrans on the basis of their morphology, according to the description of Sher (1970) and by molecular identification (Anthoine & Mugniéry, 2005). The group of each N. aberrans population was defined, according to the definition of Manzanilla-López et al (2002), by the ability, or not, to develop on bean, chilli pepper, potato, sugar beet and tomato.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular studies have suggested that N. aberrans sensu Reid et al (2003) is the major species, whereas N. bolivianus (regarded as a synonym of N. aberrans by some authors) is apparently restricted to Bolivia (Castillo et al, 2012). Subsequent studies (Anthoine and Mugniéry, 2005;Lax et al, 2007;Vovlas et al, 2007) have provided molecular evidence to support the existence of at least two major clades within South American Nacobbus. However, a consensus has yet to be achieved on the applicability of molecular diagnostics at species level, and hence most populations and quarantine interceptions will probably still be labelled as N. aberrans sensu Sher, despite mounting evidence to the contrary (Castillo et al, 2012).…”
Section: Nacobbus Aberransmentioning
confidence: 98%
“…L’étude a été réalisée sur deux populations de N. aberrans : la population N1 originaire de Bolivie (La Paz, Aroma), isolée à partir de racines de pomme de terre et la population N5 originaire d’Argentine isolée à partir de racines de tomate. Ces deux populations ont été identifiées comme N. aberrans selon des critères morphologiques (Sher, 1970), mais aussi par test moléculaire (Anthoine & Mugniéry, 2005a). Elles ont été maintenues sous serre en conditions de confinement S2 sur des plants de tomate ( Lycopersicon esculentum ) var.…”
Section: Matériel Et Méthodesunclassified